Pengaruh Media Permainan Stacking Blocks terhadap Perkembangan Kognitif Anak Kelompok B di TK Telkom Gorontalo - Ridianti Maloho; Mohamad Zubaidi; Sulastya Ningsih (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to identify the effect of the Stacking Blocks game on the cognitive development of early childhood students at TK Telkom Gorontalo. The background of this research is based on the initial condition of children who showed variations in their ability to recognize colors, shapes, sizes, as well as basic concepts of grouping and arranging objects. Educational games such as Stacking Blocks are believed to serve as an enjoyable yet effective alternative for cognitive stimulation. This study employed an experimental method with a One Group Pre-Test Post-Test design. The research sample consisted of 15 children aged 5 to 6 years, both boys and girls. The research instrument was an observation sheet of children's cognitive development, which included indicators of recognizing, naming, classifying, and arranging blocks according to color, shape, size, and balance strategies. The treatment was conducted over eight sessions, each lasting 60–120 minutes. Data were analyzed using a t-test to determine the difference between pre-test and post-test results. The findings indicated an increase in the average score from 31.6 on the pre-test to 38.733 on the post-test, where the t-count value (14.10) was higher than the t-table value (2.145). These results demonstrate that the Stacking Blocks game has a significant effect on the cognitive development of early childhood students. Thus, it can be concluded that the use of Stacking Blocks provides effective cognitive stimulation and supports the development of thinking, grouping, and problem-solving abilities in young children at TK Telkom Gorontalo